Optical Clearing Agents for Optical Imaging Through Cartilage Tympanoplasties: A Preclinical Feasibility Study. Issue 4 (2nd April 2022) - Wang, Junzhe; Chawdhary, Gaurav; Yang, Xiaojie; Morin, Francis; Khalid-Raja, Mamoona; Farrell, Joshua; MacDougall, Dan; Chen, Fangyi; Morris, David P.; Adamson, Robert B. A.
Abstract : Hypothesis: Optical clearing agents (OCAs) can render cartilage tympanoplasty grafts sufficiently transparent to permit visualization of middle ear structures in an operated ear using optical coherence tomography (OCT) imaging. Methods: Pieces of human tragal cartilage were treated with glycerol, a commonly used OCA. A reference reflector was imaged with OCT through the tympanoplasty as it cleared and the optical attenuation of the graft was measured. The reversibility of clearing and the dimensional changes associated with glycerol absorption were also measured. In a separate experiment, a human cadaveric temporal bone was prepared to simulate an ossiculoplasty surgery with cartilage replacement of the tympanic membrane. A partial ossicular replacement prosthesis (PORP) inserted in the ear was imaged with OCT through a 0.4mm cartilage graft optically cleared with glycerol. Main Outcome Measure: The optical attenuation of 0.4mm cartilage grafts decreased at 2.3+/−1.1 dB/min following treatment with glycerol, reaching a total decrease in attenuation of 13.6+/−5.9 dB after 7 minutes. The optical and dimensional effects of glycerol absorption were reversable following saline washout. In the temporal bone preparation, treatment of a cartilage graft with glycerol resulted in a 13 dB increase in signal-to-noise ratio and a 13 dB increase in contrast for visualizing the PORP through the graft with OCT. Conclusions: Optical clearing agents offer a potential pathway towards optical coherence tomography imaging of the middle ear in post-surgical ears with cartilage grafts.